SERVICE QUALITY SI MUDHA (SIMPANAN MUDHARABAH) PERSPEKTIF ISLAMIC ECONOMIC - Widya Ratna Sari; Dijan Novia Saka; Agus Subandono (Fakultas Syariah IAIN Kediri, 2022)
Service Quality is the main foundation for the growth of an activity. Moreover, Islamic financial institutions are engaged in services. This study aims to look at the Service Quality Si Mudha (Simpanan Mudharabah) in terms of Islamic Economics in Koperasi Syariah Serba Usaha Harum Dhaha Kediri. Using a qualitative approach, this type of research is a case study. The method of obtaining data is through observation, interviews, and documentation which is finally analyzed using data reduction, data presentation, and drawing conclusions. The results of Service Quality carried out with a family system and have implemented five Service Quality determinants, namely: reliability, responsiveness, assurance, empathy, tangible, all of which have been carried out well. It is proven that there is an increase in members Si Mudha (Simpanan Mudharabah) from 2018 to 2021. Meanwhile, when viewed from the perspective of Islamic economics, it has not met the scale of Sharia Economic principles, namely: professional attitudes at work have not been fully formed because there are still some miscommunications between employees and members. The trust has not been covered because there are still delays in shuttle services, especially Si Mudha (Simpanan Mudharabah) The work ethic is also not optimal because it is seen from the professional and trustworthy principles in working that there are still problems. There should be regular evaluation of each performance and a clear division of tasks, so that Service Quality can be carried out optimally. Considering that members are the driving points, Service Quality polishing must be packaged properly. Keywords: Service Quality, Mudharabah, Islamic Economic